PENGEMBANGAN BAHAN AJAR FISIKA SMA TENTANG PENGUKURAN RESISTANSI BATUBARA, KAOLIN, DAN ANDESIT DENGAN METODE RESISTIVITAS MENGGUNAKAN KONSEP LISTRIK DINAMIS - Rahayu, Made Sari; ., Partono (Jurnal Pendidikan Fisika, 2014)
The research wasdone insenior high school(SMA/MA). Observations and interviewsin senoir high (SMA)in Seputih Raman, showedthat physicâs teachers havenât developed studentâs knowledge about lessons are teached include give examples daily aplication of lesson are teached by them. Include physicâs lesson about dinamisâselectricity. So, base onthe descriptionneed todo research on thedevelopment of physicâs materialteachingfor senior high school about measuring coal, kaolin, and andesit resistance by resistivity method usedinamisâs electricity concept . The research is development research by design physicâs materialteachingfor senior high school about measuring coal, kaolin, and andesit resistance by resistivity method usedinamisâs electricity concept, then tested its feasibilityby physicâs experts and base on studentâs respons and reparation. Base on the result of research, expert test to feasibility and easy to understand the material at 79,2%, and studentâs respons in the school to teaching material at 81,9%. Base on teh result, so can be concluted that there is teaching materialfeasibility that had been developed and appropriate to use in learning. Advice from researcher, it is hoped thatthefurther development soarrangeddinamisâs electricityteaching material is better in materialâs explianing and the development.